Veterans and Agent Orange: Update 11 (2018) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
From 1962 to 1971, the U.S. military sprayed herbicides over Vietnam to strip the thick jungle canopy that could conceal opposition forces, to destroy crops that those forces might depend on, and to clear tall grasses and bushes from the perimeters of US base camps and outlying fire-support bases. Mixtures of 2,4-dichlorophenoxyacetic acid (2,4-D), 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), picloram, and cacodylic acid made up the bulk of the herbicides sprayed. The main chemical mixture sprayed was Agent Orange, a 50:50 mixture of 2,4-D and 2,4,5-T. At the time of the spraying, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), the most toxic form of dioxin, was an unintended contaminant generated during the production of 2,4,5-T and so was present in Agent Orange and some other formulations sprayed in Vietnam. Because of complaints from returning Vietnam veterans about their own health and that of their children combined with emerging toxicologic evidence of adverse effects of phenoxy herbicides and TCDD, the National Academies of Sciences, Engineering, and Medicine was asked to perform a comprehensive evaluation of scientific and medical information regarding the health effects of exposure to Agent Orange, other herbicides used in Vietnam, and the various components of those herbicides, including TCDD. Updated evaluations were conducted every two years to review newly available literature and draw conclusions from the overall evidence. Veterans and Agent Orange: Update 11 (2018) examines peer-reviewed scientific reports concerning associations between various health outcomes and exposure to TCDD and other chemicals in the herbicides used in Vietnam that were published between September 30, 2014, and December 31, 2017, and integrates this information with the previously established evidence database.
Keywords: Health and Medicine

Exploring Lessons Learned from a Century of Outbreaks: Readiness for 2030: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In November 2018, an ad hoc planning committee at the National Academies of Sciences, Engineering, and Medicine planned two sister workshops held in Washington, DC, to examine the lessons from influenza pandemics and other major outbreaks, understand the extent to which the lessons have been learned, and discuss how they could be applied further to ensure that countries are sufficiently ready for future pandemics. This publication summarizes the presentations and discussions from both workshops.
Keywords: Health and Medicine

Criteria for Selecting the Leading Health Indicators for Healthy People 2030 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Every ten years, the Department of Health and Human Service’s Healthy People Initiative develops a new set of science-based, national objectives with the goal of improving the health of all Americans. Defining balanced and comprehensive criteria for healthy people enables the public, programs, and policymakers to gauge our progress and reevaluate efforts towards a healthier society. Criteria for Selecting the Leading Health Indicators for Healthy People 2030 makes recommendations for the development of Leading Health Indicators for the initiative’s Healthy People 2030 framework. The authoring committee’s assessments inform their recommendations for the Healthy People Federal Interagency Workgroup in their endeavor to develop the latest Leading Health Indicators. The finalized Leading Health Indicators will establish the criteria for healthy Americans and help update policies that will guide decision-marking throughout the next decade. This report also reviews and reflects upon current and past Healthy People materials to identify gaps and new objectives.
Keywords: Health and Medicine; Behavioral and Social Sciences

Faith–Health Collaboration to Improve Community and Population Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
On March 22, 2018, the National Academies of Sciences, Engineering, and Medicine convened a workshop to examine the collaboration between the faith and health sectors, and to highlight the unique opportunities these collaborations offer to help improve population health outcomes. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Exploring Tax Policy to Advance Population Health, Health Equity, and Economic Prosperity: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine’s Roundtable on Population Health Improvement has been focused on the subject of dependable resources for population health since its inception in 2013. On December 7, 2017, the roundtable convened a workshop to explore tax policy as it relates to advancing population health, health equity, and economic prosperity. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Exploring Early Childhood Care and Education Levers to Improve Population Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On September 14, 2017, the Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore the intersection of health and early childhood care and education, two key social determinants of health. This workshop follows a 2014 roundtable workshop that considered the interface between the education and health sectors broadly, from research and metrics to cross-sectoral partnerships and financing. The 2017 workshop continued that discussion, with a deeper focus on early childhood (birth through age 5) as a critical period in human development and an important opportunity for educational and related interventions. This publication summarizes the presentations and discussions from the 2017 workshop.
Keywords: Health and Medicine

Global Health Transitions and Sustainable Solutions: The Role of Partnerships: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On June 13–14, 2018, the National Academies of Sciences, Engineering, and Medicine convened a multistakeholder workshop to examine the transitions affecting global health and innovative global health solutions. The goal of bringing these two topics together was to collectively explore models for innovative partnerships and private-sector engagement with the potential to support countries in transition. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Integrating Oral and General Health Through Health Literacy Practices: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Oral health care and medical health care both seek to maintain and enhance human health and well-being. Yet, dentistry and primary care in the United States are largely separated and isolated from each other. Each has its own siloed systems for education, service delivery, financing, and policy oversight. The result has been duplication of effort, a cultural gap between the two professions, and lost opportunities for productive collaboration and better health. On December 6, 2018, in Washington, DC, the National Academies of Sciences, Engineering, and Medicine held a workshop titled Integrating Oral and General Health Through Health Literacy Practices. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Principles and Obstacles for Sharing Data from Environmental Health Research: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On March 19, 2014, the National Academies of Sciences, Engineering, and Medicine held a workshop on the topic of the sharing of data from environmental health research. Experts in the field of environmental health agree that there are benefits to sharing research data, but questions remain regarding how to effectively make these data available. The sharing of data derived from human subjects—making them both transparent and accessible to others—raises a host of ethical, scientific, and process questions that are not always present in other areas of science, such as physics, geology, or chemistry. The workshop participants explored key concerns, principles, and obstacles to the responsible sharing of data used in support of environmental health research and policy making while focusing on protecting the privacy of human subjects and addressing the concerns of the research community. Principles and Obstacles for Sharing Data from Environmental Health Research summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Investing in Interventions That Address Non-Medical, Health-Related Social Needs: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
With U.S. health care costs projected to grow at an average rate of 5.5 percent per year from 2018 to 2027, or 0.8 percentage points faster than the gross domestic product, and reach nearly $6.0 trillion per year by 2027, policy makers and a wide range of stakeholders are searching for plausible actions the nation can take to slow this rise and keep health expenditures from consuming an ever greater portion of U.S. economic output. While health care services are essential to heath, there is growing recognition that social determinants of health are important influences on population health. Supporting this idea are estimates that while health care accounts for some 10 to 20 percent of the determinants of health, socioeconomic factors and factors related to the physical environment are estimated to account for up to 50 percent of the determinants of health. Challenges related to the social determinants of health at the individual level include housing insecurity and poor housing quality, food insecurity, limitations in access to transportation, and lack of social support. These social needs affect access to care and health care utilization as well as health outcomes. Health care systems have begun exploring ways to address non-medical, health-related social needs as a way to reduce health care costs. To explore the potential effect of addressing non-medical health-related social needs on improving population health and reducing health care spending in a value-driven health care delivery system, the National Academies of Science, Engineering, and Medicine held a full-day public workshop titled Investing in Interventions that Address Non-Medical, Health-Related Social Needs on April 26, 2019, in Washington, DC. The objectives of the workshop were to explore effective practices and the supporting evidence base for addressing the non-medical health-related social needs of individuals, such as housing and food insecurities; review assessments of return on investment (ROI) for payers, healthy systems, and communities; and identify gaps and opportunities for research and steps that could help to further the understanding of the ROI on addressing non-medical health-related social needs. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Gulf War and Health: Volume 11: Generational Health Effects of Serving in the Gulf War - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
For the United States, the 1991 Persian Gulf War was a brief and successful military operation with few injuries and deaths. However, soon after returning from duty, a large number of veterans began reporting health problems they believed were associated with their service in the Gulf. At the request of Congress, the National Academies of Sciences, Engineering, and Medicine has been conducting an ongoing review of the evidence to determine veterans' long-term health problems and potential causes. Some of the health effects identified by past reports include post-traumatic stress disorders, other mental health disorders, Gulf War illness, respiratory effects, and self-reported sexual dysfunction. Veterans' concerns regarding the impacts of deployment-related exposures on their health have grown to include potential adverse effects on the health of their children and grandchildren. These concerns now increasingly involve female veterans, as more women join the military and are deployed to war zones and areas that pose potential hazards. Gulf War and Health: Volume 11 evaluates the scientific and medical literature on reproductive and developmental effects and health outcomes associated with Gulf War and Post-9/11 exposures, and designates research areas requiring further scientific study on potential health effects in the descendants of veterans of any era.
Keywords: Health and Medicine

Global Health and the Future Role of the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
While much progress has been made on achieving the Millenium Development Goals over the last decade, the number and complexity of global health challenges has persisted. Growing forces for globalization have increased the interconnectedness of the world and our interdependency on other countries, economies, and cultures. Monumental growth in international travel and trade have brought improved access to goods and services for many, but also carry ongoing and ever-present threats of zoonotic spillover and infectious disease outbreaks that threaten all. Global Health and the Future Role of the United States identifies global health priorities in light of current and emerging world threats. This report assesses the current global health landscape and how challenges, actions, and players have evolved over the last decade across a wide range of issues, and provides recommendations on how to increase responsiveness, coordination, and efficiency – both within the U.S. government and across the global health field.
Keywords: Health and Medicine

Exploring Medical and Public Health Preparedness for a Nuclear Incident: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine held a workshop on August 22–23, 2018, in Washington, DC, to explore medical and public health preparedness for a nuclear incident. The event brought together experts from government, nongovernmental organizations, academia, and the private sector to explore current assumptions behind the status of medical and public health preparedness for a nuclear incident, examine potential changes in these assumptions in light of increasing concerns about the use of nuclear warfare, and discuss challenges and opportunities for capacity building in the current threat environment. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

The Role of Nonpharmacological Approaches to Pain Management: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Pain is a leading cause of disability globally. The dramatic increase in opioid prescriptions within the past decade in the United States has contributed to the opioid epidemic the country currently faces, magnifying the need for longer term solutions to treat pain. The substantial burden of pain and the ongoing opioid crisis have attracted increased attention in medical and public policy communities, resulting in a revolution in thinking about how pain is managed. This new thinking acknowledges the complexity and biopsychosocial nature of the pain experience and the need for multifaceted pain management approaches with both pharmacological and nonpharmacological therapies. The magnitude and urgency of the twin problems of chronic pain and opioid addiction, combined with the changing landscape of pain management, prompted the National Academies of Sciences, Engineering, and Medicine to convene a workshop on December 4–5, 2018, in Washington, DC. The workshop brought together a diverse group of stakeholders to discuss the current status of nonpharmacological approaches to pain management, gaps, and future directions. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Implications of the California Wildfires for Health, Communities, and Preparedness: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
California and other wildfire-prone western states have experienced a substantial increase in the number and intensity of wildfires in recent years. Wildlands and climate experts expect these trends to continue and quite likely to worsen in coming years. Wildfires and other disasters can be particularly devastating for vulnerable communities. Members of these communities tend to experience worse health outcomes from disasters, have fewer resources for responding and rebuilding, and receive less assistance from state, local, and federal agencies. Because burning wood releases particulate matter and other toxicants, the health effects of wildfires extend well beyond burns. In addition, deposition of toxicants in soil and water can result in chronic as well as acute exposures. On June 4-5, 2019, four different entities within the National Academies of Sciences, Engineering, and Medicine held a workshop titled Implications of the California Wildfires for Health, Communities, and Preparedness at the Betty Irene Moore School of Nursing at the University of California, Davis. The workshop explored the population health, environmental health, emergency preparedness, and health equity consequences of increasingly strong and numerous wildfires, particularly in California. This publication is a summary of the presentations and discussion of the workshop.
Keywords: Health and Medicine

The Convergence of Infectious Diseases and Noncommunicable Diseases: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On June 11 and June 12, 2019, the National Academies convened a workshop to explore the growing understanding of how the interplay between humans and microbes affects host physiology and causes noncommunicable diseases. Discussions included an overview of colliding epidemics, emerging research on associations between infectious and noncommunicable diseases, risks posed by chronic diseases to the development and severity of infectious diseases, and the influence of the microbiome. Workshop participants also examined the challenges and opportunities of convergence, the integration of health care delivery models and interventions, potential approaches for research, policy, and practice in the immediate-term, and potential directions for the long-term. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Health Risks of Indoor Exposure to Particulate Matter: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The U.S. Environmental Protection Agency (EPA) defines PM as a mixture of extremely small particles and liquid droplets comprising a number of components, including "acids (such as nitrates and sulfates), organic chemicals, metals, soil or dust particles, and allergens (such as fragments of pollen and mold spores)". The health effects of outdoor exposure to particulate matter (PM) are the subject of both research attention and regulatory action. Although much less studied to date, indoor exposure to PM is gaining attention as a potential source of adverse health effects. Indoor PM can originate from outdoor particles and also from various indoor sources, including heating, cooking, and smoking. Levels of indoor PM have the potential to exceed outdoor PM levels. Understanding the major features and subtleties of indoor exposures to particles of outdoor origin can improve our understanding of the exposure–response relationship on which ambient air pollutant standards are based. The EPA's Indoor Environments Division commissioned the National Academies of Sciences, Engineering, and Medicine to hold a workshop examining the issue of indoor exposure to PM more comprehensively and considering both the health risks and possible intervention strategies. Participants discussed the ailments that are most affected by particulate matter and the attributes of the exposures that are of greatest concern, exposure modifiers, vulnerable populations, exposure assessment, risk management, and gaps in the science. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Management of Legionella in Water Systems - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Legionnaires' disease, a pneumonia caused by the Legionella bacterium, is the leading cause of reported waterborne disease outbreaks in the United States. Legionella occur naturally in water from many different environmental sources, but grow rapidly in the warm, stagnant conditions that can be found in engineered water systems such as cooling towers, building plumbing, and hot tubs. Humans are primarily exposed to Legionella through inhalation of contaminated aerosols into the respiratory system. Legionnaires' disease can be fatal, with between 3 and 33 percent of Legionella infections leading to death, and studies show the incidence of Legionnaires' disease in the United States increased five-fold from 2000 to 2017. Management of Legionella in Water Systems reviews the state of science on Legionella contamination of water systems, specifically the ecology and diagnosis. This report explores the process of transmission via water systems, quantification, prevention and control, and policy and training issues that affect the incidence of Legionnaires' disease. It also analyzes existing knowledge gaps and recommends research priorities moving forward.
Keywords: Health and Medicine; Earth Sciences

Genomic Epidemiology Data Infrastructure Needs for SARS-CoV-2: Modernizing Pandemic Response Strategies - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
In December 2019, new cases of severe pneumonia were first detected in Wuhan, China, and the cause was determined to be a novel beta coronavirus related to the severe acute respiratory syndrome (SARS) coronavirus that emerged from a bat reservoir in 2002. Within six months, this new virus—SARS coronavirus 2 (SARS-CoV-2)—has spread worldwide, infecting at least 10 million people with an estimated 500,000 deaths. COVID-19, the disease caused by SARS-CoV-2, was declared a public health emergency of international concern on January 30, 2020 by the World Health Organization (WHO) and a pandemic on March 11, 2020. To date, there is no approved effective treatment or vaccine for COVID-19, and it continues to spread in many countries. Genomic Epidemiology Data Infrastructure Needs for SARS-CoV-2: Modernizing Pandemic Response Strategies lays out a framework to define and describe the data needs for a system to track and correlate viral genome sequences with clinical and epidemiological data. Such a system would help ensure the integration of data on viral evolution with detection, diagnostic, and countermeasure efforts. This report also explores data collection mechanisms to ensure a representative global sample set of all relevant extant sequences and considers challenges and opportunities for coordination across existing domestic, global, and regional data sources.
Keywords: Health and Medicine

Long-Term Health Monitoring of Populations Following a Nuclear or Radiological Incident in the United States: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Accidents and terrorist attacks that lead to the release of radioactive materials can cause deaths, injuries, and a range of psychosocial effects in the surrounding community and team of emergency responders. In the United States, federal, state, and local agencies respond with the necessary resources to address the consequences of nuclear and radiological incidents and monitor the affected population. Following the 2011 Fukushima Daiichi Nuclear Power Plant accident and the 2017 Gotham Shield National Level Exercise, the CDC recognized an opportunity to improve their practices by establishing a more efficient and timely health effect surveillance system before another incident occurs. On March 12-13th, 2019, the National Academies convened a workshop to discuss the process for preparing a radiation registry for monitoring long-term health effects of populations affected by a nuclear or radiological incident. Participants assessed existing information, useful practices, and tools for planning a radiation registry that will enhance incident monitoring and response methods. This publication summarizes the discussions and presentations from the workshop.
Keywords: Health and Medicine; Environment and Environmental Studies